APCCAS 2008 - 2008 IEEE Asia Pacific Conference on Circuits and Systems 2008
DOI: 10.1109/apccas.2008.4746191
|View full text |Cite
|
Sign up to set email alerts
|

Efficient time varying frequency tracking using recursive estimation

Abstract: This paper presents performance results of an algorithm for efficient time varying frequency estimation and tracking. The algorithm is implemented with a small number of multiplications, which is important for most hardware implementations. A correlation based Pulse-Pair (PP) method is used for the initial frequency estimation. The PP method requires inverse tan operation that can be implemented using an efficient recursive technique. A simulation example showing proper frequency estimation and compensation fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Simulations in [7] discuss the error performance of the recursive frequency estimation algorithm implemented using a forgetting factor λ , when the frequency 0 f of the signal is a constant. It has been shown that an estimator using a lag value m equal to a third of the signal length asymptotically achieves the CRB.…”
Section: Efficient Recursive Implementationmentioning
confidence: 99%
See 2 more Smart Citations
“…Simulations in [7] discuss the error performance of the recursive frequency estimation algorithm implemented using a forgetting factor λ , when the frequency 0 f of the signal is a constant. It has been shown that an estimator using a lag value m equal to a third of the signal length asymptotically achieves the CRB.…”
Section: Efficient Recursive Implementationmentioning
confidence: 99%
“…A simple and efficient recursive technique to implement the inverse tan operation in the PP method has been reported recently in [5] using the CORDIC (COordinate Rotation DIgital Computer) architecture [6]. The extension of the PP method to frequency estimation and tracking of signals where the instantaneous frequency (IF) is time varying is reported by us in [7]. The tracking is performed with the use of a simple, efficient chirp rate estimator implemented via state-space modeling [8].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation